Activities in Retirement: The Role of Motivational and Situational Characteristics - Maxin, Leena Maren (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2012)
Against the backdrop of aging populations, labor shortages, and a longer healthy life expectancy, there has recently been considerable discussion of the great potential that post-retirement activities hold for individuals, organizations, and society alike. This dissertation consists of three empirical papers investigating the life reality of active retirees in Germany. In addition, framework conditions and motivational structures that need to be considered in creating jobs for this group of workers are examined. The first paper identifies the prerequisites for productivity after retirement age and describes the changed nature of modern-day retirement. Current levels of post-retirement work are quantified by reference to German Microcensus data. The data show that adults continue to engage in paid employment beyond the applicable retirement age, with self-employment and unpaid work in family businesses making up the greatest share of post-retirement activities. Qualitative data collected from 146 active retirees (mean age = 67 years, standard deviation = 4) showed that the changes entailed in retirement include more flexible structures in everyday life. Content analysis revealed that reasons for taking up post-retirement activities were the desire to help, pass on knowledge, or remain active; personal development and contact with others; and a desire for appreciation and recognition. In addition, flexible working hours and the freedom to make decisions are evidently important aspects that need to be taken into account in creating employment activities for silver workers. The second paper extends the findings of the first paper by investigating the differences that respondents experienced between their former career job and their post-retirement activities, drawing on an additional quantitative sample of active retirees (N = 618, mean age = 69 years, standard deviation = 4). Factor analysis revealed differences in four areas: First, differences were identified in person-related variables, such as work ability. Second, differences were perceived in the scope of the job itself with regard to workers’ tasks, skills, or job function. Third, the perceived freedom of time allocation and flexibility in job practice distinguished between the silver job and the former career job. Fourth, differences were noted in perceived responsibility and in the significance of the activity. The third paper further examined how relevant personal motivational goals (achievement, appreciation, autonomy, contact, and generativity) as well as corresponding occupational characteristics of the silver job were related to life and work satisfaction in the quantitative sample (N = 661, mean age = 69 years, standard deviation = 4). Hierarchical regression analyses showed that the motivational goals of achievement, appreciation, autonomy, contact, and generativity significantly predicted life satisfaction, whereas only generativity predicted work satisfaction. With respect to the occupational characteristics, none of the situational predictors influenced life satisfaction, but opportunities to fulfill one’s achievement goals, to pass on knowledge, and to experience appreciation and autonomy predicted work satisfaction. The results suggest that post-retirement workers seem to differentiate between perceived life satisfaction and work satisfaction as two independent constructs. In conclusion, key motives for taking up post-retirement activities were generativity (the wish to help and pass on knowledge), but also personal development, appreciation, autonomy, and contact. The findings indicate that organizations should introduce flexible working hours, and offer silver workers advisory and freelance work. Providing freedom to make decisions and ensuring due appreciation of the contribution made by silver workers will lead to a fruitful interplay of silver workers and organizations. Future research should build on these findings by applying longitudinal designs and drawing on samples of retirees with more diverse educational and financial backgrounds. The papers of this dissertation echo the call for a new, more positive way of looking at the capacities of active retirees.

Vor dem Hintergrund steigender gesunder Lebenserwartung und des erwarteten Fachkräftemangels werden Aktivitäten im Ruhestand als großes Potenzial sowohl für Organisationen und Gesellschaft als auch für die betroffenen Personen selbst diskutiert. Diese Dissertation besteht aus drei empirischen Arbeiten (Artikeln), die die Lebensrealität aktiver Rentner, so genannter Silver Worker, in Deutschland erforschen. Genauer werden Rahmenbedingungen und Motivstrukturen untersucht, die bei der Gestaltung von Arbeit für diese Personengruppe berücksichtigt werden sollten. Der erste Artikel benennt die grundsätzlichen Voraussetzungen für Produktivität im Rentenalter und beschreibt die veränderte Bedeutung des Ruhestands. Das aktuelle Ausmaß an Erwerbstätigkeit im Rentenalter wird anhand von Mikrozensusdaten quantifiziert. Ergebnisse zeigen, dass auch jenseits des geltenden Renteneintrittsalters noch Erwerbsarbeit besteht, überwiegend von Selbstständigen und mithelfenden Familienangehörigen. Die inhaltsanalytische Auswertung einer qualitativen Studie (N = 146, Ø-Alter = 67 Jahre) weist darauf hin, dass sich mit dem Eintritt in den Ruhestand der Alltag in Richtung flexiblerer Strukturen verändert. Entscheidende Beweggründe bei der Aufnahme einer Tätigkeit im Ruhestand sind helfen, Wissen weitergeben, aktiv bleiben wollen, Weiterentwicklung, Kontakt sowie der Wunsch nach Wertschätzung und Anerkennung. Flexible Arbeitszeitgestaltung und Entscheidungsfreiheit stellen wesentliche Elemente bei der Gestaltung von nachberuflichen Tätigkeiten dar. Der zweite Artikel erweitert die qualitativen Ergebnisse aus dem ersten Artikel, indem die erlebten Unterschiede der beruflichen Tätigkeit vor dem Eintritt in den Ruhestand und den Tätigkeitsmerkmalen der Aktivität im Ruhestand in einer zusätzlichen, quantitativen Stichprobe (N = 618, Ø-Alter = 69) untersucht werden. Die faktorenanalytische Auswertung ergab vier Faktoren, die Unterschiede zwischen der früheren beruflichen Tätigkeit und der aktuellen Aktivität im Ruhestand beschreiben: Erstens in personenbezogenen Variablen wie Arbeits- und Leistungsfähigkeit, zweitens in der Art der Tätigkeit, drittens in den erlebten Freiheitsgraden und viertens im wahrgenommenen Ausmaß der Verantwortung. Der dritte Artikel untersucht die Zusammenhänge von motivationalen Zielen (Anerkennung, Autonomie, Kontakt, Leistung und Weitergabe) und den thematisch korrespondierenden Tätigkeitsmerkmalen mit Lebens- und Arbeitszufriedenheit in der quantitativen Stichprobe (N = 661, Ø-Alter 69). Hierarchische Regressionsanalysen zeigen, dass alle motivationalen Ziele signifikante Prädiktoren für Lebenszufriedenheit darstellen, aber nur Weitergabe einen signifikanten Zusammenhang mit Arbeitszufriedenheit aufzeigt. In Bezug auf die Tätigkeitsmerkmale erweist sich keines als Prädiktor für Lebenszufriedenheit, wobei die Möglichkeiten Wissen weiterzugeben, Erfolg zu sehen, sowie Wertschätzung und Autonomie zu erfahren einen signifikanten Zusammenhang mit Arbeitszufriedenheit aufweisen. Die Ergebnisse lassen vermuten, dass Silver Worker zwischen der erlebten Lebens- und Arbeitszufriedenheit als unterschiedliche Konstrukte unterscheiden. Zusammenfassend lässt sich aus den Ergebnissen der Artikel ableiten, dass Organisationen flexible Arbeitszeitmodelle einführen bzw. ausbauen und Silver Workern beratende und freiberufliche Tätigkeiten anbieten sollten. Dabei sind Entscheidungsfreiheit und Wertschätzung des Beitrags der Silver Worker wesentlich. Weitere Forschung sollte auf diesen Ergebnissen aufbauend längsschnittliche Untersuchungen anschließen und aktive Rentner mit unterschiedlichen Bildungshintergründen und finanzieller Ausstattung mit einbeziehen. Die Artikel dieser Dissertation unterstreichen die Forderung eines neuen, positiveren Blicks auf die Potenziale aktiver Rentner. Die Dissertation ist in englischer Sprache verfasst.
Tätigkeiten im Ruhestand - Motivation und Rahmenbedingungen
Keywords: Older Worker; Work Motivation; Retirement; Älterer Arbeitnehmer; Arbeitsmotivation; Ruhestand; 330 Wirtschaft